2017
DOI: 10.7863/ultra.16.03059
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Precision of Sonography of the Lumbar Multifidus and Transversus Abdominis During Dynamic Activities

Abstract: Objectives To determine the intrarater reliability and precision of lumbar multifidus and transversus abdominis thickness measurements using freehand sonography in a range of static and dynamic conditions. Methods Fifteen asymptomatic participants performed a range of exercises while sonography was used to measure absolute muscle thickness and changes in muscle thickness from rest. Exercise conditions included the abdominal drawing‐in maneuver, active straight leg raise, contralateral arm lift, both unloaded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
11
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 32 publications
10
11
1
2
Order By: Relevance
“…In the present study, there were no statistically significant differences observed in the musculus transversus abdominis thickness values during each assessed activity, though the average muscle thickness among healthy women was higher than in the group of women with SUI symptoms -a similar finding to the results of the study by Madokoro et al [22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, there were no statistically significant differences observed in the musculus transversus abdominis thickness values during each assessed activity, though the average muscle thickness among healthy women was higher than in the group of women with SUI symptoms -a similar finding to the results of the study by Madokoro et al [22].…”
Section: Discussionsupporting
confidence: 90%
“…The reliability, validity and safety of ultrasound imaging as a means of assessment of abdominal muscle thickness, for example in order to evaluate muscle activity, has been borne out by several past clinical studies [21][22][23][24]. Moreover, the ultrasound imaging is still the part of the "gold standard" in the gynaecological imaging options [25].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that US measurements of muscle thickness and CR in participants with and without NCLBP during static and dynamic positions exhibit good to high reliability. These results are consistent with the available literature on US measurements of TA and LM muscles thickness [31,32].…”
Section: Discussionsupporting
confidence: 93%
“…K. C. Gibbon і співавт. [21] провели дослідження точності вимірювань товщини паравертебральних м'язів за допомогою УСГ, в результаті якого дійшли висновку про достатню надійність цього методу, хоча він і поступається МРТ [22]. Під час сканування здорових тканин за допомогою УСГ візуалізують чітку фасцикулярну структуру м'язів: м'язові волокна мають низьку ехогенність (тобто виглядають практично чорними), а сполучнотканинні елементи (перимізій та епімізій)підвищену (виглядають практично білими) [23].…”
unclassified